2014
DOI: 10.1002/jor.22769
|View full text |Cite
|
Sign up to set email alerts
|

Muscle optimization techniques impact the magnitude of calculated hip joint contact forces

Abstract: In musculoskeletal modelling, several optimization techniques are used to calculate muscle forces, which strongly influence resultant hip contact forces (HCF). The goal of this study was to calculate muscle forces using four different optimization techniques, i.e., two different static optimization techniques, computed muscle control (CMC) and the physiological inverse approach (PIA). We investigated their subsequent effects on HCFs during gait and sit to stand and found that at the first peak in gait at 15–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 28 publications
3
43
0
1
Order By: Relevance
“…Predictions of hip joint contact forces are affected by the optimization approach used to solve the neuromuscular redundancy problem (Modenese et al, 2011; Wesseling et al, 2015). Wesseling et al found that static optimization was the most favorable approach for obtaining accurate predictions, and Bosmans et al used this approach while predicting hip joint contact forces in children with cerebral palsy (Bosmans et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Predictions of hip joint contact forces are affected by the optimization approach used to solve the neuromuscular redundancy problem (Modenese et al, 2011; Wesseling et al, 2015). Wesseling et al found that static optimization was the most favorable approach for obtaining accurate predictions, and Bosmans et al used this approach while predicting hip joint contact forces in children with cerebral palsy (Bosmans et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…), hip (Blanco & Gambini, ; Blemker & Delp, ; Wesseling et al. ) and shoulder (Nikooyan et al. ; Seth et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although sophisticated musculoskeletal models of the knee (Beidokhti et al 2016), hip (Blanco & Gambini, 2006;Blemker & Delp, 2005;Wesseling et al 2015) and shoulder (Nikooyan et al 2011;Seth et al 2016;Wu et al 2016) have been developed in the past, a complete model of the hand is still lacking. One of the main reasons for this is the high complexity of the human hand.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have explored several computational approaches to address the muscle redundancy problem. The most common approach found in the literature is static optimization, where a cost function is minimized one time frame at a time to find muscle forces that reproduce experimental joint moments calculated via inverse dynamics [8][9][10][11]. Musculoskeletal models used in this process are typically scaled versions of generic models available in the literature [12,13].…”
Section: Introductionmentioning
confidence: 99%